The Role of Microglia and Astrocytes in Huntington’s Disease - Palpagama, Thulani H.; Waldvogel, Henry J.; Faull, Richard L. M.; Kwakowsky, Andrea (Frontiers in Molecular Neuroscience, 2019)
Huntington’s disease (HD) is an autosomal dominant neurodegenerative disease. HD patients present with movement disorders, behavioral and psychiatric symptoms and cognitive decline. This review summarizes the contribution of microglia and astrocytes to HD pathophysiology. Neuroinflammation in the HD brain is characterized by a reactive morphology in these glial cells. Microglia and astrocytes are critical in regulating neuronal activity and maintaining an optimal milieu for neuronal function. Previous studies provide evidence that activated microglia and reactive astrocytes contribute to Huntington’s disease pathology through transcriptional activation of pro-inflammatory genes to perpetuate a chronic inflammatory state. Reactive astrocytes also display functional changes in glutamate and ion homeostasis and energy metabolism. Astrocytic and microglial changes may further contribute to the neuronal death observed with the progression of HD. Importantly, the degree to which these neuroinflammatory changes are detrimental to neurons and contribute to the progression of HD pathology is not well understood. Furthermore, recent observations provide compelling evidence that activated microglia and astrocytes exert a variety of beneficial functions that are essential for limiting tissue damage and preserving neuronal function in the HD brain. Therefore, a better understanding of the neuroinflammatory environment in the brain in HD may lead to the development of targeted and innovative therapeutic opportunities.